AUTHOR’S POSITION OF THE ENGLISH WRITER T. SMOLLET IN THE NOVEL "THE EXPEDITION OF HUMPHRY CLINKER" - Jalilova, Khurshida (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
This article is devoted to the analysis of the identification of the author's position in the novel "The Journey of Humphrey Clinker" by Tobias Smollett, a representative of the English literature of the XVIII century. Comparing the epistolary novel "The Expedition of Humphry Clinker" with a non-fiction work based on Smollett’s real journey "Travels through France and Italy", it was found that these two works are similar in genre and subject matter since they complement each other. In addition, the form of Smollett’s novel is close to the epistolary novels of other European writers of the Enlightenment. However, in this work, one event or case is described not by one, but by several addressees of letters, which can be considered a kind of experiment of the writer. Smollett, as an educator, focuses on the issues of science and education, culture and literature. Through the letters of the protagonist of the novel, Matthew Bramble, the author, using humor, satire and irony, highlights the pressing problems of his time. In conclusion, it is revealed that it is this image in the work that expresses the author's position and his ideas of Enlightenment.
Keywords: travel genre; epistolary novel; non-fiction; author; author's position; image; character; letter; enlightenment; idea